HERBARIUM SPECIMENS OF WILD CHILEAN POTATO SPECIES BELONGING TO THE SECTION PETOTA DUMORT. GENUS SOLANUM L. IN THE VIR HERBARIUM - I. G. Chukhina; E. A. Krylova; A. B. Ovchinnikova; T. A. Gavrilenko (Труды по прикладной ботанике, генетике и селекции, 2018)
A revision of herbarium specimens of Chilean potato species belonging to the section Petota Dumort. genus Solanum L. was conducted. The VIR herbarium [WIR] has 25 specimen sheets of five species: Solanum leptostigma Juz., S. maglia Schlechtd., S. molinae Juz., S. ochoanum Lechn., S. zykinii Lechn. Authentic materials from S.V. Yuzepczuk and V.S. Lehnovich have been identified, namely syntypes of S. molinae , S. ochoanum and S. zykinii. The neotypification of S. leptostigma was done.